Crafting Utopia Anda: Lokakarya Boneka Kertas (Bepe-Bepean) untuk Menginspirasi Pemberdayaan Pemuda Pengungsi Melalui Kreasi Seni Bersama - Muhammad Arfan Achmad; Akhmad Taufiq; Qonita Afnani Firdaus; Meirina Triharini; Amira Rahardiani (Jurnal Desain Indonesia., 2026)
Indonesia has yet to ratify the 1951 Refugee Convention and the 1967 Protocol, which has led to various challenges for refugees in Indonesia, ranging from uncertain legal status to limited access to basic services. The conventional approaches offered through available solutions often fail to address and meet the needs of refugees. Mental health issues among refugees in Indonesia, particularly among young refugees, have become a major concern, stemming from traumatic experiences faced in their home countries, during the transition to transit countries like Indonesia, challenges in adapting to new environments, and the rejection experienced due to negative stigma. Conditions such as depression, anxiety, PTSD, and other mental health disorders are common, yet access to mental health support remains severely limited. Furthermore, the stigma surrounding mental health further hinders individuals like young refugees from seeking help. This results in young refugees losing motivation to continue their daily lives in transit countries like Indonesia. The Crafting Your Utopia through Paper Doll workshop aims to harness the strength of imagination and creativity among young refugees to inspire them to explore their potential and strengthen their vision for the future through paper doll activities (bepe-bepean). This workshop encourages participants to collaboratively build their ideal utopia. This utopia is not defined by beauty or sophistication but is an ideal vision created by the strength and self-potential, as well as the support gained from the diverse visions and abilities of young refugees. Through bepe-bepean and play activities, participants imagine their lives ten years into the future, projecting their potential and aspirations not only for themselves but also for their communities and environments. This collaborative process emphasizes the importance of creating an inclusive and supportive future, where each individual contributes their strengths to build a shared vision and become agents of change. This workshop utilizes a framework created for these activities called Utopia: Imagining and Creating, which combines the utopian approach as a method (Utopia as a method) for imaginative reconstruction of existing social orders. The framework consists of two steps: Imagining and Creating, and applies a co-creation method in the creation step. The workshop leverages the imagination and creative thinking of young refugees through collaborative and innovative approaches aimed at motivating them and reminding them of dreams that have been forgotten due to mental health challenges. The hope is that by motivating them and rekindling their dreams, young refugees can live meaningfully during their prolonged stay in Indonesia before their resettlement to third countries. Additionally, the utopian approach as a method aims to encourage critical reflection on the current conditions of young refugees, thereby opening up spaces for critique and alternative ideas on how the conditions of refugee communities should be shaped. Keywords: Refugees, Utopia as a Method, Paper Doll, Co-creation